2015
DOI: 10.1021/acsami.5b08964
|View full text |Cite
|
Sign up to set email alerts
|

Modulated UiO-66-Based Mixed-Matrix Membranes for CO2 Separation

Abstract: Mixed-matrix membranes (MMMs) composed of polyimide (PI) and metal-organic frameworks (MOFs) were synthesized using Matrimid as the polymer and zirconium terephthalate UiO-66 as the filler. The modulation approach, combined with the use of amine-functionalized linkers, was used for synthesis of the MOF fillers in order to enhance the intrinsic separation performance of the MOF and improve the particle-PI compatibility. The presence of amine groups on the MOF outer surface introduced either through the linker, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
155
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(164 citation statements)
references
References 68 publications
7
155
0
2
Order By: Relevance
“…Apparently, the crystals of UiO66-NH 2 were formed in a ball shape and particle size was about 200 nm. These features were also discussed by Luu Cam Loc et al [25] and Anjum et al [26]. Figure 1c displayed the thermogravimetric analysis (TGA) result of the obtained UiO66-NH 2 .…”
Section: Xrd Pattern Insupporting
confidence: 74%
“…Apparently, the crystals of UiO66-NH 2 were formed in a ball shape and particle size was about 200 nm. These features were also discussed by Luu Cam Loc et al [25] and Anjum et al [26]. Figure 1c displayed the thermogravimetric analysis (TGA) result of the obtained UiO66-NH 2 .…”
Section: Xrd Pattern Insupporting
confidence: 74%
“…To better understand why Ti–UiO‐66‐H and Ti–UiO‐66‐D exhibited enhanced catalytic activity in the ODS reaction of DBT, a model for the structure of UiO‐66(Zr) before and after Ti ion exchange was proposed (Scheme ). It is known that most of Zr sites in the structure of high‐crystallinity UiO‐66‐H are well coordinated by O and Cl ions . As a result, UiO‐66‐H exhibited low ODS activity (5.6 % yield of DBTO 2 ), which can be attributed to the lack of active sites.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that most of Zr sites in the structure of high-crystallinity UiO-66-H are well coordinated by Oa nd Cl ions. [37,38] As ar esult, UiO-66-H exhibited low ODS activity (5.6 %y ield of DBTO 2 ), whichc an be attributedt ot he lack of active sites.…”
Section: Relationship Between Structure and Catalytic Performancementioning
confidence: 91%
“…The results showed that the combination of the amine‐functionalized modulator and linker in UiO‐66‐NH 2 ‐ABA gave the best performance among the MMMs with different filler/modulator combinations. The MMMs with 30 wt % filler loading (CO 2 permeability: 38 Barrer, CO 2 /CH 4 selectivity: 48) were over 50 % more selective and 540 % more permeable than the reference Matrimid membrane (CO 2 permeability: 6 Barrer, CO 2 /CH 4 selectivity: 31) as well as 30 % and 140 % more selective and permeable, respectively, than MMMs based on the reference UiO‐66 (CO 2 permeability: 16 Barrer, CO 2 /CH 4 selectivity: 36) …”
Section: Emerging Directionsmentioning
confidence: 98%